Návrh na zajištění finanční stability podniku - Lukášová, Klára (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Diplomová práce hodnotí finanční zdraví konkrétního podniku v letech 2002 – 2005 na základě vybraných metod finanční analýzy. Obsahuje návrhy možných řešení zjištěných problémů, které mají vést ke zlepšení finanční situace a zajištění finanční stability podniku v budoucích letech.

This thesis asses the financial health of the company in the years 2002 – 2005 at the basis of sesected methods of the financial analysis. It comprieses proposals of possible solutions of identified problems which should result in the improvement of financial situation and ensurance of financial stability of the firm in future years.
The Proposal for Ensurance of Financial Stability of the Firm
Keywords: finanční analýza; finanční situace; finanční stabilita; financial analysis; financial situation; financial stability